Age Differences in Attention Lapses Mask Age Differences in Memory Failures: A Methodological Note on Suppression - Cheyne, James A.; Carriere, Jonathan S.; Smilek, Dan (Frontiers in Psychology, 2013)
Although objective measures of memory performance typically indicate memory declines with age, self-reported memory failures often show no relation to age. In contrast, self-reported attention failures are reliably negatively correlated with age. This contrast suggests the possibility that age-related awareness and reporting of memory failures might be masked by a concurrent decrease in attention failures, which would reduce encoding failures with age and hence reduce perceived memory failures. Self-reported problems of attention and memory were evaluated in two samples with the ages spanning eight decades. Initial analysis indicated that attention failures significantly decreased with age, whereas memory problems did not to differ across age. The association of self-reported memory failures became significantly positive, however, when residualized on attention lapses. In contrast, the correlation between attention lapses and age was modestly affected when memory failures were controlled. These results highlight the close relation of attention lapses and memory problems and, beyond the implications of individual differences in attention for memory research, suggest the advisability of assessing attention failures for a full evaluation of memory problems.